2020
DOI: 10.3390/cells9081845
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Defective Response to Infection Involves Autophagy and Lipid Metabolism

Abstract: Cystic fibrosis (CF) is a hereditary disease, with 70% of patients developing a proteinopathy related to the deletion of phenylalanine 508. CF is associated with multiple organ dysfunction, chronic inflammation, and recurrent lung infections. CF is characterized by defective autophagy, lipid metabolism, and immune response. Intracellular lipid accumulation favors microbial infection, and autophagy deficiency impairs internalized pathogen clearance. Myriocin, an inhibitor of sphingolipid synthesis, significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Indeed, we showed that Myr promotes a TFEB-induced stress response. TFEB initiates a transcriptional program that reduces inflammation and oxidative stress, induces autophagy [ 45 , 51 ], organizes cellular lipids by increasing their oxidation [ 45 , 51 , 52 ] but also by favoring lipid storage formation [ 8 ]. These activities all contribute to reducing most of the cellular lipid species [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we showed that Myr promotes a TFEB-induced stress response. TFEB initiates a transcriptional program that reduces inflammation and oxidative stress, induces autophagy [ 45 , 51 ], organizes cellular lipids by increasing their oxidation [ 45 , 51 , 52 ] but also by favoring lipid storage formation [ 8 ]. These activities all contribute to reducing most of the cellular lipid species [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, evidence suggests that the airway tract microbiota, thick secretions, and autophagy induction in CF patients may play a protective role against viral infections. Autophagy, as an immune mechanism in CF disease, could be heightened and actively contributes to the antiviral response (van Ewijk et al, 2005 ; Junkins et al, 2014 ; Mingione et al, 2020 ; Pehote and Vij, 2020 ).…”
Section: Replication Of Sarscov-2; Outcome In Cf Patientsmentioning
confidence: 99%
“…DHA, like other long-chain n-3 fatty acids, are alo transferred to special pro-solving lipid mediators (SPM), e.g., the resolvins, maresins and protectins, of importance to balance inflammation provided by the ARA metabolites [94]. The role of SPM in regulating autophagy, which is defective in CF, may be a possible therapeutic option against 136 the persistent inflammation [95][96][97]. That was supported by adding resolvin D1 to infected CF KO mice and in studies of cells from CF patients [98].…”
Section: Fatty Acid Abnormalities In Cfmentioning
confidence: 99%